Overview of evolutionary modeling algorithms for contract scheduling - Hrybkov, Serhii; Kozhushko, Illia (My University, 2023)
The analysis was carried out to determine the advantages and disadvantages between the algorithms and to define the best solution that can be used to support the planning of contract execution.
Keywords: empirical research method; evolutionary modeling algorithms; genetic algorithm; bee colony algorithm; ant colony algorithm; information technologies; інформаційні технології; емпіричний метод; еволюційне моделювання; генетичний алгоритм; алгоритм бджолиної колонії; алгоритм мурашиної колонії; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки